A HISTORICAL–CONCEPTUAL ANALYSIS OF INTEGRATING INTERNATIONAL ASSESSMENT STUDIES INTO NATIONAL EDUCATION POLICY - Akramjon Matkarimov (Journals Park Publishing, 2025)
This article examines the conceptual underpinnings of the Programme for International Student Assessment (PISA) and traces how international large-scale assessments have been formed, evolved, and aligned with education policy. It outlines the historical stages in the emergence of assessment concepts; the coherence between assessment frameworks and national policy agendas; the role of the Organisation for Economic Co-operation and Development (OECD) as the developer and steward of the PISA concept; and the critical perspectives surrounding these frameworks. The analysis highlights implications for national education systems, including the use of international methodologies and indicators to inform measurement tools, curricular materials, and strategic directions. [5, 266]
Keywords: PISA international assessment program; conceptual framework; national education system; student literacy; education quality.